PEMBERDAYAAN MASYARAKAT ADAT DALAM PENGOBATAN TRADISIONAL (BATTRA) BERBASIS TRANSCULTURAL NURSING CARE (TNC) SEBAGAI UPAYA MENINGKATKAN KESEHATAN JANTUNG DI DESA LOK BUNTAR - Mohtar, M. Sobirin; Meldawati; Rahmadani; Muhammad Rifa'i; Sari, Ririn Anggita; Revi; Nahda Laili Khairizqa; Pratama, Prasetya Putra; Ningsih, Kristiyana Wahyu (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The Indigenous Community Group and health cadres of Lok Buntar Village are partners in the Community Partnership Empowerment program. This group consists of several traditional medicine experts (BATTRA) for heart attacks. The village community, mostly farmers, tend to choose traditional medicine due to limited internet access and the distance to the hospital. However, the high mortality rate indicates the need for increased knowledge of heart health. Through the assistance of cadres, they are expected to educate the community using the Transcultural Nursing Care approach. (TNC). The goal is to enhance the knowledge and skills of the cadres, as well as empower the indigenous community in addressing heart health issues. The implementation methods are: planning, action, observation, and evaluation. The average level of knowledge among cadres increased from a high category (82.22%) to a higher level (93.33%), while the community's initial low level (43.33%) improved to a moderate level (75%). A culturally-based approach and ongoing support are expected to help the village community achieve better overall heart health. This is a positive step towards community empowerment and sustainable improvement in quality of life.